2017
DOI: 10.2337/dc17-1096
|View full text |Cite
|
Sign up to set email alerts
|

How Does Empagliflozin Reduce Cardiovascular Mortality? Insights From a Mediation Analysis of the EMPA-REG OUTCOME Trial

Abstract: OBJECTIVEIn the BI 10773 (Empagliflozin) Cardiovascular Outcome Event Trial in Type 2 Diabetes Mellitus Patients (EMPA-REG OUTCOME) trial involving 7,020 patients with type 2 diabetes and established cardiovascular (CV) disease, empagliflozin given in addition to standard of care reduced the risk of CV death by 38% versus placebo (hazard ratio [HR] 0.62 [95% CI 0.49, 0.77]). This exploratory mediation analysis assesses the extent to which treatment group differences in covariates during the trial contributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
536
2
18

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 588 publications
(577 citation statements)
references
References 33 publications
(36 reference statements)
21
536
2
18
Order By: Relevance
“…In addition, empagliflozin exerts the same beneficial cardiovascular effects after adjustment for ischaemic risk factors (blood pressure, low‐density lipoprotein cholesterol, HbA1c) . In a mediation analysis of this trial, changes in haematocrit (and haemoglobin) but not HbA1c appeared to be the variables with the largest impact on the risk of cardiovascular death . This argues strongly against glycaemic control as the underlying cardio‐protective mechanism .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, empagliflozin exerts the same beneficial cardiovascular effects after adjustment for ischaemic risk factors (blood pressure, low‐density lipoprotein cholesterol, HbA1c) . In a mediation analysis of this trial, changes in haematocrit (and haemoglobin) but not HbA1c appeared to be the variables with the largest impact on the risk of cardiovascular death . This argues strongly against glycaemic control as the underlying cardio‐protective mechanism .…”
Section: Introductionmentioning
confidence: 80%
“…Interestingly, in a non‐diabetic mouse model of afterload‐induced HF, empagliflozin prevented worsening of left ventricular function . Overexpression and activation of Ca 2+ /calmodulin‐dependent kinase II (CaMKII) are hallmarks of HF and also found in diabetic patients, leading to increased diastolic Ca 2+ leak from the sarcoplasmic reticulum (SR) and reduced SR Ca 2+ load, causing contractile dysfunction and arrhythmias . Interestingly, CaMKII is activated by increased cytosolic Ca 2+ concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, small but significant differences in HbA1c, in favour of the groups allocated to SGLT‐2 inhibitors or GLP‐1 agonists, were observed, with greater differences in HbA1c in the GLP‐1 agonist trials. A follow‐up mediation analysis of the EMPA‐Reg trial has further suggested that only a modest proportion (23%‐29%) of the overall cardiovascular benefit was attributable to glucose lowering . A further mediation analysis of the SUSTAIN 6 trial has also raised concerns regarding the magnitude and rapidity with which glucose levels are lowered given the unexpected increased risk of retinopathy reported .…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the rapid onset of benefit seen may be due to plasma volume and preload reduction, and notably there was a 5% increase in haematocrit in the EMPA‐REG OUTCOME trial. Our findings are consistent with the results of a recent mediation analysis of the EMPA‐REG OUTCOME trial showing that haematocrit mediated around 50% of the effect of empagliflozin versus placebo on the risk of cardiovascular death …”
Section: Discussionmentioning
confidence: 99%